VD_FINDINFO Décision / 2019 / 979 vom 2. Dezember 2019 - VD Tribunal cantonal (2019)
CONFLIT D'INTÉRÊTS, AVOCAT, CHOIX DE L'AVOCAT, INDÉPENDANCE DE L'AVOCAT, PRÉVENU | 12 let. c LLCA, 127 al. 3 CPP (CH)